Study of Modern Balinese Style Design Forms on Greeting Cards by Putu Pageh - Swandi, I Made Dwiarya; Narayana, I Gede; Darmada, I Made; Paramartha, Adhi; Lodra, I Nyoman (Sean Institute, 2025)
Putu Pageh, a Balinese designer, brings local nuances with a modern touch in the greeting card design 'Selamat Hari Raya Galungan dan Kuningan'. This design features unique visual exploration that distinguishes it from others, making it an interesting subject for research. This study aims to identify the characteristics of Modern Balinese design in the context of graphic design. A qualitative method was used through observation, documentation, literature study, and questionnaires, with thematic analysis based on several visual categories. The study results indicate that the characteristics of Modern Balinese Design in this greeting card lie in the representation of Barong Ket - Rangda combined with jejaitan/tamiang as a symbol of Galungan and Kuningan. The use of pastel colors conveys a celebratory expression with three main colors and their variations through tint/shade techniques. The character illustration is decorative and simplified, incorporating Form Generator's scientific thinking, particularly in the letterform derived from jejaitan/tamiang. This Modern Balinese Design style inspires designers to innovate while maintaining local values. Further research can explore other communication media and audience responses to Modern Balinese style design.